Simulating the impact of crossover kidney transplantation on the nord italia transplant program - Monica Salvioli; Roberto Lucchetti; Rosanna Torelli (Games, 2016)
The increasing number of patients affected by chronic kidney disease makes it necessary to rely on living donors. However, a patient often cannot exploit her potential donor, due to blood or tissue incompatibility. Therefore, crossover transplantation programs have been developed in several countriesin order to increase the number of people receiving a kidney from a living donor. After reviewing the essential medical facts needed for the subsequent results, we quickly introduce two known algorithms for crossover transplantation. Next, we consider a dataset provided by the Nord Italia Transplant program, and we apply the above algorithms in order to highlight the benefits of these efficient procedures.
Keywords: 330; kidney transplantation; living donor; dichotomous preferences; priority mechanism; TTCC; cycles and chains